Vascular Shunts in Civilian Trauma - Abou Ali, Adham N.; Salem, Karim M.; Alarcon, Louis H.; Bauza, Graciela; Pikoulis, Emmanuel; Chaer, Rabih A.; Avgerinos, Efthymios D. (Frontiers in Surgery, 2017)
Experience with temporary intravascular shunts (TIVS) for vessel injury comes from the military sector and while the indications might be clear in geographically isolated and under resourced war zones, this may be an uncommon scenario in civilian trauma. Data supporting TIVS use in civilian trauma has been extrapolated from the military literature where it demonstrated improved life and limb salvage. Few non-comparative studies from the civilian literature have also revealed similar favorable outcomes. Still, TIVS placement in civilian vascular injuries is uncommon and by some debatable given the absence of clear indications for placement, the potential for TIVS-related complications, the wide-spread resources for immediate and definitive vascular repair, and the need for curtailing costs and optimizing resources. This article reviews the current evidence and the role of TIVS in contemporary civilian trauma management.